2018
DOI: 10.1111/hsc.12548
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with prescribed medicines in community health services in China: A cross-sectional survey 6 years after the implementation of the national essential medicines policy

Abstract: The National essential medicines policy (NEMP) is promoted by the World Health Organization for affordable medicines that can meet the basic needs of communities.Patient acceptance is essential for achieving the policy goals of the NEMP. This study aimed to assess patient satisfaction with prescribed medicines in community health services under the NEMP context in China. A stratified random sampling strategy was adopted to select 1,037 participants in 40 community health centres from four provinces in China. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A systematic review has summarized the domains used for patient satisfaction measurement in Saudi Arabia, which includes communication attributes, relational conduct, technical skill, personal qualities, availability, and accessibility [12]. Meanwhile, many empirical studies have been conducted to measure patient satisfaction in different countries, such as England [13], Pakistan [14,15], China [16,17,18,19,20], Germany [21], Saudi Arabia [22], the U.S. [23], Canada [24], Italy [25], and South Africa [26]. Among these studies, multifarious measures were employed and numerous determinants of patient satisfaction were identified.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review has summarized the domains used for patient satisfaction measurement in Saudi Arabia, which includes communication attributes, relational conduct, technical skill, personal qualities, availability, and accessibility [12]. Meanwhile, many empirical studies have been conducted to measure patient satisfaction in different countries, such as England [13], Pakistan [14,15], China [16,17,18,19,20], Germany [21], Saudi Arabia [22], the U.S. [23], Canada [24], Italy [25], and South Africa [26]. Among these studies, multifarious measures were employed and numerous determinants of patient satisfaction were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitation management is at the core of preventing possible disease recurrence, saving medical costs, and improving patients' care satisfaction 18–23 . Previous research has indicated that patients who are older, with a lower level of educational attainment, and covered by health insurance tend to have better care satisfaction 24 …”
Section: Literature Reviewmentioning
confidence: 99%
“…[18][19][20][21][22][23] Previous research has indicated that patients who are older, with a lower level of educational attainment, and covered by health insurance tend to have better care satisfaction. 24…”
Section: The Contracted Family Doctor System In Chinamentioning
confidence: 99%
“…This is evidenced by 11 monographs/textbooks and an impressive 173 peer-reviewed publications produced by the CHP staff about the Chinese health system and health reforms published in both English and the Chinese language. Topics have included patient satisfaction (29)(30)(31), medications policy and practice (32)(33)(34)(35)(36)(37)(38)(39)(40), patient safety and organizational safety culture (41,42), health reform (35,(43)(44)(45)(46)(47)(48)(49)(50), health insurance (50)(51)(52), emergency response (53)(54)(55)(56), and human resource management (3).…”
Section: The China Health Program Outcomesmentioning
confidence: 99%